Khasiat tanaman lidah buaya dalam perawatan kulit dan kesehatan rambut - Syarafina, Ainassabih Liwani (Maliki Interdisciplinary Journal, 2024)
The aloe vera plant (Aloe vera) has long been known for its various benefits for skin care and hair health. The purpose of this article is to examine the benefits of the aloe vera plant for healthy skin and hair. The method used is a literature study where the author uses various literature to obtain research data and uses a qualitative approach because the data produced is in the form of descriptions. The largest composition of aloe vera gel is water, which reaches 99.5%, while the rest consists of solids such as polysaccharides, vitamins, minerals, organic acids and phenolic compounds. Aloe vera gel provides great benefits for skin health, especially in terms of accelerating wound healing, moisturizing and smoothing the skin, and hydrating dry and chapped skin. Apart from its benefits for the skin, aloe vera is also known for its benefits in caring for hair. Aloe vera gel helps increase blood circulation to the scalp, strengthens hair follicles, and reduces dandruff and itchy scalp. The vitamins and minerals contained in aloe vera are important for maintaining overall hair health. Through its antioxidant properties, aloe vera helps fight free radicals that damage hair follicles, thereby strengthening existing hair and encouraging new hair growth. Thus, aloe vera is not only useful for daily care, but also has potential as a natural therapy for more complex skin and hair problems.